A third dose of the BNT162b2 mRNA vaccine sufficiently improves the neutralizing activity against SARS-CoV-2 variants in liver transplant recipients - Tomiyama, Takahiro; Suzuki, Rigel; Harada, Noboru; Tamura, Tomokazu; Toshida, Katsuya; Kosai-Fujimoto, Yukiko-; Tomino, Takahiro; Yoshiya, Shohei; Nagao, Yoshihiro; Takeishi, Kazuki; Itoh, Shinji; Kobayashi, Nobuhiro; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
We examined the neutralizing antibody production efficiency of the second and third severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine doses (2nd- and 3rd-dose) and neutralizing activity on mutant strains, including, the Ancestral, Beta and Omicron strains using green fluorescent protein-carrying recombinant SARS-CoV-2, in living-donor liver transplantation (LDLT) recipients. The patients who were administered vaccines other than Pfizer-BioNTech○RBNT162b2 and who had coronavirus disease 2019 in this study period were excluded. We enrolled 154 LDLT recipients and 50 healthy controls. The median time were 21 days (between 1st and 2nd vaccination) and 244 days (between 2nd and 3rd vaccination). The median neutralizing antibody titer after 2nd-dose was lower in LDLT recipients than in controls (0.46 vs 1.00, P<0.0001). All controls had SARS-CoV-2 neutralizing antibodies, whereas 39 LDLT recipients (25.3%) had no neutralizing antibodies after 2nd-dose; age at vaccination, presence of ascites, multiple immunosuppressive treatments, and mycophenolate mofetil treatment were significant risk factors for non-responder. The neutralizing activities of recipient sera were approximately 3-fold and 5-fold lower than those of control sera against the Ancestral and Beta strains, respectively. The median antibody titer after 3rd-dose was not significantly different between recipients and controls (1.02 vs 1.22, p=0.0758); only 5% recipients was non-responder. The neutralizing activity after third dose to Omicron strains were enhanced and had no significant difference between two groups. Only the 2nd-dose was not sufficiently effective in recipients; however, 3rd-dose had sufficient neutralizing activity against the mutant strain and was as effective as that in healthy controls.